The mysterious case of the C. elegans gut granule: death fluorescence, anthranilic acid and the kynurenine pathway - Gems, David; Coburn, Cassandra (Frontiers in Genetics, 2013)
Despite decades of research on the nematode C. elegans, it still contains many hidden secrets. One such is the function of the prominent organelles known as gut granules, which are numerous in the intestinal cells of nematodes throughout the suborder Rhabditina. A striking feature of gut granules is the blue fluorescence that they emit under ultraviolet light. Clues to gut granule function include their acidic interior and capacity for endocytosis, both lysosome-like features (though gut granules are much bigger than normal lysosomes). This and the fluorescent material within identify gut granules as lysosome-like organelles (LROs), akin to pigment-containing melanosomes in mammals and eye pigment granules in Drosophila. Thus, the identity of the blue fluorescent substance could provide a key to understanding gut granule function.